The Revolutionary Coordinating Junta: A Frustrated Project of Guerrilla Convergence (Comillas Journal of International Relations, 2023)
The following work deals with the project of guerrilla convergence that supposed, from 1974, the Revolutionary Coordinating Junta (JCR). This, made up of several guerrillas from Argentina, Bolivia, Chile, and Uruguay, is the first effort to generate a supranational confrontation mechanism against the authoritarian drifts taking place in the Southern Cone. However, it was blurred to a very residual plane and, in any case, full of contradictions and pressing weaknesses. In this regard, the work tries to explain the factors and elements that justify their rapid disappearance, illustrating the central argument with documentation prepared by the armed groups themselves. This, available at the Armed Movements Documentation Center or at the “David Cámpora” Archive of Armed Struggle in Montevideo.
Keywords: National Liberation Army; Revolutionary Coordinating Junta; Revolutionary Left Movement; National Liberation Movement-Tupamaros; Workers’ Revolutionary Party – People’s Army